High Performance Building Façade Solutions-Phase II - Eleanor S. Lee; Brian E. Coffey; Luis L. Fernandes; Sabine Hoffmann; Andrew McNeil; Anothai Thanachareonkit; Gregory J. Ward (2014)
The High Performance Building Façade Solutions–Phase II project was initiated through the California Energy Commission’s Public Interest Energy Research (PIER) program in July 2010 to support industry’s development and deployment of both incremental and breakthrough façade technologies in partnership with the U.S. Department of Energy (DOE). The objective of this three-year project was to develop, or support the development and deployment of, promising near-term and emerging zero net energy building façade technologies for solar control and daylighting, addressing two of the largest end uses in California commercial buildings: cooling and lighting. In partnership with industry (such as manufacturers), three classes of technologies were investigated: daylighting systems, angular-selective shading systems, and dynamic façade systems. Commercially available and emerging prototype technologies were developed and evaluated using laboratory tests. Simulations, full-scale outdoor tests in the Advanced Window Testbed, and demonstration projects quantified energy and peak electric demand reductions and occupant satisfaction, acceptance, and comfort associated with the resultant indoor environment. Several new technologies were developed using virtual prototyping tools. Integrated control systems were developed using model predictive controls. Simulation tools were developed to model operable complex fenestration systems such as shades and microprismatic films. A schematic design tool called COMFEN was developed to facilitate evaluation of these advanced technologies in the early design phase. All three classes of technologies resulted in significant reductions in perimeter zone energy use and peak electric demand, providing viable options that can support California’s long-term goal of achieving zero net energy use in the next decade.
Keywords: automated shading; between-pane shading; bidirectional scattering distribution functions; building energy simulation tools; Complex fenestration systems; daylighting; daylighting simulation tools; electrochromics; exterior shading; goniophotometer; light shelves; microprismatic films; model predictive controls; motorized shading; shading; solar-optical properties; switchable windows; thermochromics; virtual prototyping; window heat transfer

Automated Production of Optimization-Based Control Logics for Dynamic Façade Systems, with Experimental Application to Two-Zone External Venetian Blinds - Brian E. Coffey; Andrew McNeil; Thierry Stephane Nouidui; Eleanor S. Lee (2013)

A Post-Occupancy Monitored Evaluation of the Dimmable Lighting, Automated Shading, and Underfloor Air Distribution System in The New York Times Building - Eleanor S. Lee; Luis L. Fernandes; Brian E. Coffey; Andrew McNeil; Robert D. Clear; Thomas L. Webster; Fred S. Bauman; Darryl J. Dickerhoff; David Heinzerling; Tyler Hoyt (Lawrence Berkeley National Laboratory, 2013)
With aggressive goals to reduce national energy use and carbon emissions, the US Department of Energy will be looking to exemplary buildings that have already invested in new approaches to achieving the energy performance goals now needed at a national level. The New York Times Building, in New York, New York, incorporates a number of innovative technologies, systems and processes and could become a model for widespread replication in new and existing buildings. Post-occupancy data are invaluable in establishing confidence in innovation. A year-long monitored study was conducted to verify energy performance, assess occupant comfort and satisfaction with the indoor environment, and evaluate impacts on maintenance and operations. Lessons learned were derived from the analysis; these lessons could help identify and shape policy, financial, or supporting strategies to accelerate diffusion in the commercial building market.

Integrated control of operable fenestration systems and thermally massive HVAC systems: Methods and simulation studies of energy savings potential - Brian E. Coffey (2012)
The future design of high performance buildings is expected to involve more active facade technologies, acting in intelligent collaboration with the HVAC and lighting systems to produce comfortable indoor environments with reduced energy consumption. Integrated control of active facade systems and HVAC is challenging, particularly with thermally-massive HVAC systems such as radiant floors and ceilings. This paper describes methods for devising near-optimal controllers for such integrated systems, allowing for any arbitrary level of complexity in the facade system. An offline-optimization approximation to model predictive control is used with a model consisting of a reduced- order approximation of the zone and HVAC thermal properties and an interpolation grid of the daylight and solar gains attributes of the facade in its various possible states. The optimization over the 24-hour prediction horizon is split into two levels, with GenOpt used at the top level to deal with the complexity of the facade, alongside a linear programming solution to the chilled slab control. The model can be calibrated to match monitored data, or some combination of whole-building energy modeling and Radiance outputs. To test the methods and to estimate energy savings potential, case studies were performed with a calibrated model based on an EnergyPlus ASHRAE 90.1-2010 office building, modi ed to use radiant slabs and operable Venetian blinds (either internal or external) or electochromic glazing. Results are shown for four US climates. Further research is discussed.

Model-based controls for integrated shading and UFAD control: Report on initial studies - Brian E. Coffey; Eleanor S. Lee (2011)
Methods and initial results are described for model-based controls with offline optimization for integrated shading and UFAD control for an office building in New York. Two cases are studied through lookup-table calculation and annual simulation of the resulting controllers: one case with interior blinds, the other case with exterior blinds. The interior blind case was found to reduce HVAC energy by 5% over a simple baseline control, and the exterior blind case produced a 5.6% HVAC energy savings over the baseline. Further investigations and case studies are planned.
Keywords: cloud computing; integrated controls; Model predictive control (MPC); offline optimization; shading and HVAC controls

Modeling solar heat gains of complex fenestration systems using bidirectional scattering distribution functions - Thierry Stephane Nouidui; Andrew McNeil; Christian Kohler; Brian E. Coffey; Eleanor S. Lee (2011)